Fabrication Aids for Cold Straightening I-Girders - Gergess, Antoine; Sen, Rajan (Engineering Journal, 2004)
Fabrication out-of-straightness in steel girders can be rectified using heat straightening or cold straightening. While heat straightening has been extensively researched, little information is available on cold straightening where loads are used to achieve the same result. This paper provides an analytical framework for an innovative cold straightening (also referred to as cold bending) system developed by a fabricator. Maximum safe limits on loads, out-of-straightness and load frame configurations that are consistent with prevailing "Load and Resistance Factor Design" (LFRD) criteria are proposed. Fabrication aids for Grade 250 (Fy = 36 ksi) and 345 (Fy = 50 ksi) steel are developed and their application illustrated by three numerical examples.